Moderate and severe injuries at five international olympic-style wrestling tournaments during 2016-2019 - Molnár, S.; Hunya, Z.; Gáspár, K.; Szerb, I.; Szabó, N.; Mensch, K.; Körösi, E.; Bacskai, K.; Sántha, Á. K.; Janka, E. A.; Shadgan, B. (Journal of Sports Science & Medicine, 2022)
As a contact sport, wrestling may result in injuries. Based on the severity, they are classified as mild, moderate, severe and critical. All injuries occurring at international competitions are documented in a cloud-based surveillance system. The purpose of this study was to analyze the incidence and characteristics of moderate and severe (including critical) wrestling injuries that occurred during five international Olympic-style wrestling competitions in 2016-2019. Three Wrestling World Championships and two European Wrestling tournaments were organized by the Hungarian Wrestling Federation in 2016-2019. A total of 2483 wrestlers in three Olympic wrestling styles have competed in 3007 matches. Data from all injuries were recorded and analyzed to define rates, locations, types and severity, and to compare with previous reports. A total of 53 wrestlers sustained 55 injuries, which is equivalent to an overall injury incidence rate of 9.1‰ (9.1/1000 athletic exposures). Greco-Roman and Women Wrestling had the same injury incidence rate, while Freestyle had a lower one (9.5‰ versus 8.5‰). The injury proportion by regions and anatomic locations were on head and face 29.1%, spine and trunk 16.4 % and the upper-and-lower extremity injuries equally 27.3%. The most common types of injuries included ligament lesions, joint injuries, skin lacerations, and contusions. Five wrestlers (0.8‰) sustained strangulation or concussion. Wrestling injury rates during United World Wrestling competitions are not high, but when happen they can be serious. Despite relatively low incidence rate of injuries, there is a need for continuous education for medical teams, referees and coaches to avoid wrestling injuries.